Public health implications of the relationship between socioeconomic and cultural dimensions on immunization coverage in Bangkalan, East Java - Ulfah Nurnaningsih Herya; Rachmawat Windi Chusniah; Rahmawati Indana Tri; Katmawanti Septa; Samah Dea Aflah; Wahyuni Oktavia Sri; Aulia Syafa Nairah; Az Zahra Aulia Rizqia (BIO Web of Conferences)
Compared to the statewide average of 91.7%, Bangkalan District had the lowest basic vaccination coverage in East Java in 2022, at just 64.7%. Misconceptions regarding vaccinations are the cause of this poor coverage, which raises the risk of morbidity and death. According to WHO, 1.5 million children die each year from illnesses that may be prevented because they were not vaccinated, underscoring the wider impact on public health. The socioeconomic and cultural elements influencing parents’ choices to vaccinate their children in Bangkalan were examined in this study. 87 mothers of toddlers older than two years from the Blega Health Center were chosen by simple random sampling as part of a cross-sectional study. Data were gathered using questionnaires and interviews, and SPSS 23 was used for both univariate and bivariate analysis. The findings indicated that family culture did not significantly correlate with vaccine coverage (p-value = 0.218), while socioeconomic position and immunization coverage did (p-value = 0.001). The low vaccination rates are mostly influenced by socioeconomic considerations, which emphasizes the need for increased accessibility and awareness. It is advised to implement tactics like expanding the hours of health facilities and providing vaccination services in accessible areas. In Bangkalan, increasing vaccination coverage and lowering avoidable child fatalities depend heavily on economic assistance and education.